2020
DOI: 10.1007/s11420-020-09798-w
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatic Disease-Related Symptoms during the Height of the COVID-19 Pandemic

Abstract: Background: Systemic rheumatic diseases are characterized by diverse symptoms that are exacerbated by stressors. Questions/Purposes: Our goal was to identify COVID-19-related stressors that patients associated with worsening rheumatic disease symptoms. Methods: With approval of their rheumatologists, patients at an academic medical center were interviewed with open-ended questions about the impact of COVID-19 on daily life. Responses were analyzed with qualitative methods using grounded theory and a comparativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 16 publications
2
31
0
Order By: Relevance
“…Individuals in New York City surveyed during the heightened phase of implementing transmission prevention measures reported worsening of their RMD with the changes to their daily lives regardless of SARS‐CoV‐2 infection status. Fatigue from multitasking and adherence to isolation measures may have directly contributed to disease flares 89 . Stress from uncertainties in finances, exposure to infection, and changes to RMD medication, among other issues, were indirect contributors 89 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals in New York City surveyed during the heightened phase of implementing transmission prevention measures reported worsening of their RMD with the changes to their daily lives regardless of SARS‐CoV‐2 infection status. Fatigue from multitasking and adherence to isolation measures may have directly contributed to disease flares 89 . Stress from uncertainties in finances, exposure to infection, and changes to RMD medication, among other issues, were indirect contributors 89 .…”
Section: Resultsmentioning
confidence: 99%
“…Fatigue from multitasking and adherence to isolation measures may have directly contributed to disease flares 89 . Stress from uncertainties in finances, exposure to infection, and changes to RMD medication, among other issues, were indirect contributors 89 . One study which used the Short Form 12‐item Health Survey to specifically measure QoL in a UK cohort of RMD patients, showed a worsening of physical and mental functioning during the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Although our study took place during a brief period, some patients already reported worsening symptoms and flares that they attributed to suboptimal medications and to emotional and physical upheaval caused by the pandemic (22). Glucocorticoids were often used in response because they reversed symptoms quickly and were familiar to patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with rheumatological diseases, who are prone to psychological disorders, are likely to be easily psychologically affected by the COVID-19 outbreak. Recent studies have shown that patients with RA, Axial Spondyloarthritis, Lupus, and Behçet Disease were severely affected by the COVID-19 pandemic [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, ours is the first study evaluating the psychological well-being of AS patients using the PGWB score.Many patients with rheumatological diseases are likely to be psychologically affected by the ongoing COVID-19 pandemic. Mancuso et al reported that the psychiatric complaints of patients with rheumatological diseases (a total of 112 patients with Systemic Lupus Erythematosus (SLE), RA, and Spondyloarthritis) increased significantly during the pandemic[18]. On the other hand,…”
mentioning
confidence: 99%